Toward a Standardized Reporting of Outcomes in Hand Osteoarthritis: Developing a Common Metric of Outcome Measures Commonly Used to Assess Functioning. Issue 8 (August 2016) - Prodinger, Birgit; Stamm, Tanja; Peterson, Diana; Stucki, Gerold; Tennant, Alan; ,
Abstract : Objective: Functioning is an important outcome in hand osteoarthritis (OA). The heterogeneity of patient‐reported outcome measures (PROMs) available challenges the direct comparability of information collected by these instruments. This study aimed to examine whether it is possible to achieve metric equivalence of PROMs commonly used to measure functioning in people with hand OA. Methods: A secondary analysis of data from 253 persons who participated in the Vienna Hand Osteoarthritis Cohort Study was conducted applying the Rasch measurement model. Participants completed the Health Assessment Questionnaire, the Australian/Canadian Index for Hand Osteoarthritis, the Functional Index for Hand Osteoarthritis (FIHOA), and the Cochin Scale. The assumptions of stochastic ordering, local independence, unidimensionality, and invariance were tested for each scale independently before the scales were co‐calibrated onto a common metric. Results: Except for the FIHOA, all measures indicated issues of local dependency in the initial analyses. After accommodating those with testlets, all scales satisfied the assumptions of the Rasch model (χ 2  > 0.05). Marginal misfit in 2 items was found in the FIHOA, but this did not disturb person estimates. As the 4 scales form a common metric that satisfies the assumptions of the Rasch model, the scores can be equated. Conclusion: The scores of the 4 hand function measures can be transformed to a common 0–100 metric, such that scores can be interchanged. A user‐friendly transformation table enables clinicians and researchers to have access to the common metric by simply adding up the total score for each instrument and identifying the corresponding transformed score on the common metric.